How are information and communication technologies (ICT), and social networks used in micro, small and medium enterprises (MSMEs)? case: ARICA and Parinacota Region, Chile - Bernal Peralta, Jorge (2021)
In a totally globalized world where the use of digital platforms is increasingly taking center stage, it is relevant to study the relationship of these technologies with companies and how they have influenced them. Therefore, the present research aims to characterize the use of Information and Communication Technologies (ICT) and Social Networks (RRSS) of Micro, Small and Medium Enterprises (MSMEs) advised by the Arica Business Center, Chile. In a stratified random sample (n = 120), a survey was applied to find out the knowledge, use, frequency and impact that ICT and social media have on companies. The results showed that 73% of the clients of the Arica Business Center use ICT, especially the laptop or desktop computer, which 68% declare to use it several times a day, followed with 73%, the smartphone. The greatest impact that ICT has within companies is related to communication with customers. Regarding the RRSS, 81% of the MSMEs of the Arica Business Center, declare that they use them in the company, and that Facebook is used in 70% to deliver information and news, 53% offer customer services to through WhatsApp, and 52% do not recruit workers through RRSS. The greatest impact of the RRSS in the MSMEs, is in the promotion of products and / or services, 74% of the companies which in a high rank.